Academic Resilience of Students with Disabilities in Higher Education: The Role of Peer Relationships and Academic Self-Efficacy - Miftachul Jannah; Yulina Eva Riany; Melly Latifah (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Access to higher education for students with disabilities is increasing, yet they still face challenges that impact their psychological well-being and academic performance. This study aims to analyze the role of peer relationships and academic self-efficacy on the academic resilience of students with disabilities in higher education. Using a quantitative method and voluntary sampling, 155 students with visual, hearing, and physical-motor impairments participated in an online survey from February to May 2025. Results show that while most students had positive peer relationships, these did not significantly impact academic resilience. However, academic self-efficacy had a significant positive effect on academic resilience. Peer relationships and academic self-efficacy significantly influenced academic resilience (p < 0.05). These findings highlight the key role of academic self-efficacy in promoting resilience and academic success among students with disabilities in higher education settings. Keywords: Academic resilience, peer relationships, academic self-efficacy, student with disability